2019
DOI: 10.1016/j.fertnstert.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations of different molecular forms of antimüllerian hormone and biomarkers of polycystic ovary syndrome and normal women

Abstract: Objective: To study different antim€ ullerian hormone (AMH) isoforms in women with polycystic ovary syndrome (PCOS) and healthy regularly cycling women and to investigate whether levels of AMH isoforms combined with baseline characteristics can predict PCOS. Design: Cross-sectional study. Setting: Fertility clinic. Patient(s): Eighty-eight women with PCOS and 24 age-and body mass index (BMI)-matched normal control subject women recruited from April 2010 to February 2013. AMH isoforms were analyzed in biobanked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…This might indicate that AMH C is only generated after receptor binding of the AMH N,C isoform, as shown in vitro ( 40 ). In a recent study by Wissing et al ( 41 ), it was shown that the amount of uncleaved AMH (proAMH) in normoovulatory women is only 3% of the total promature isoforms (proAMH and AMH N,C ). This result was obtained using Ansh Labs ELISAs that either use a different antibody pair or sample treatment to distinguish the different isoforms ( 41 ).…”
Section: Measurement Of Serum Amhmentioning
confidence: 99%
See 1 more Smart Citation
“…This might indicate that AMH C is only generated after receptor binding of the AMH N,C isoform, as shown in vitro ( 40 ). In a recent study by Wissing et al ( 41 ), it was shown that the amount of uncleaved AMH (proAMH) in normoovulatory women is only 3% of the total promature isoforms (proAMH and AMH N,C ). This result was obtained using Ansh Labs ELISAs that either use a different antibody pair or sample treatment to distinguish the different isoforms ( 41 ).…”
Section: Measurement Of Serum Amhmentioning
confidence: 99%
“…In a recent study by Wissing et al ( 41 ), it was shown that the amount of uncleaved AMH (proAMH) in normoovulatory women is only 3% of the total promature isoforms (proAMH and AMH N,C ). This result was obtained using Ansh Labs ELISAs that either use a different antibody pair or sample treatment to distinguish the different isoforms ( 41 ). This suggests that the majority of serum AMH levels represents cleaved AMH.…”
Section: Measurement Of Serum Amhmentioning
confidence: 99%
“…Other assays found normal concentrations of AMH corresponding to the number of follicles present (36,37), probably reflecting that the antibodies employed captured different epitopes. It is important to note that the concentration of AMH in FFs is a thousand times higher than it is in serum (38). Furthermore, some of the AMH isoforms present in FFs and GCs may be degraded in serum, explaining why we do not expect the isoform profiles detected in the follicular compartment to be reflected in serum.…”
Section: Discussionmentioning
confidence: 93%
“…It is now well recognised that serum AMH is elevated in women with PCOS ( 5 , 31 , 32 ). In a recent study, AMH exhibited high specificity:sensitivity based on the receiver-operating characteristic (ROC) curve in predicting PCOS compared with age-matched controls ( 32 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…An international collaborative study ( 7 , 8 ) was thus undertaken by the World Health Organization (WHO) to produce a reference material purified from media from a stable human ovarian cancer cell line and available in ampoules (coded 16/190), and to derive an immunopotency evaluation for this human AMH preparation. The AMH preparation consisted of the full length 140kDa form with a modification of the internal cleavage site to ensure maximum cleavage between the pro-hormone and mature forms of the molecule ( 58 ) which represent the major forms of AMH in human serum ( 14 , 15 , 32 ). The WHO study involved the distribution the WHO reference preparation to participant laboratories, along with 21 human serum samples of varying origin.…”
Section: Development Of An International Amh Reference Reagent For Immunoassaymentioning
confidence: 99%